2020
DOI: 10.1177/1557988320926743
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Opportunistic Infections and Associated Factors in HIV-Infected Men Who Have Sex With Men on Antiretroviral Therapy in Bach Mai Hospital, Hanoi, Vietnam: A Case-Control Study

Abstract: Objective: To investigate the distribution of opportunistic infections (OIs) and factors associated with acquiring OIs in human immunodeficiency virus (HIV)-infected men who have sex with men (MSM) in comparison to those of heterosexual patients. Method: A cross-sectional study was conducted on 82 HIV-infected MSM and 120 HIV-infected heterosexual men in Bach Mai Hospital, Hanoi, Vietnam. Demographical characteristics and clinical data were collected and analyzed using appropriate statistics (Mann–Whitney, Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…This finding is in line with several previous studies. 17,20,25 So, this study showed a strong association between age and acquiring OIs. However, in contrast to this finding, a study by Majigo et al found that as the age of the patient increases, the risk of acquiring an OI will decrease.…”
Section: Factors Associated With Reoccurrence Of Oismentioning
confidence: 51%
See 1 more Smart Citation
“…This finding is in line with several previous studies. 17,20,25 So, this study showed a strong association between age and acquiring OIs. However, in contrast to this finding, a study by Majigo et al found that as the age of the patient increases, the risk of acquiring an OI will decrease.…”
Section: Factors Associated With Reoccurrence Of Oismentioning
confidence: 51%
“…A cross-sectional study conducted to determine the prevalence of OIs at Bach Mai Hospital, Hanoi, Vietnam, identified that 63.4% developed OIs. 20 A study carried out in Abeokuta, Nigeria, showed that 34% of HIV/AIDS patients were infected with at least one OI. 21 The magnitude of OI developing in HIV/AIDS patients in a study conducted in Southern Tigray, Ethiopia, was 55.3%.…”
Section: Factors Associated With Reoccurrence Of Oismentioning
confidence: 99%
“…Only one study compared HCV co-infection in HIV positive MSM vs HIV positive heterosexual men attending the same HIV service. 37 Injecting drug use was more prevalent in HIV positive heterosexuals than in MSM (46.8% vs 2.4%). Consequently, HIV-HCV co-infection was higher in heterosexual males (55%) than MSM (4.9%).…”
Section: Resultsmentioning
confidence: 95%
“…A study in Vietnam showed the majority of OI among MSM and heterosexual patients were 63.4% and 81.7%, respectively. The most frequent OIs in the MSM group were human papillomavirus (HPV) (11%), followed by hepatitis B virus (8.5%), mycobacterium tuberculosis (7.3%), and talaromycosis (2.4%)( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…( 18 , 19 ). Research in Vietnam found that the prevalence of opportunistic infections in HIV patients with heterosexuals reached 81.7% ( 12 ). Opportunistic infections that can occur in heterosexual patients infected with HIV are fungal infections Cryptococcus neoformans ( 20 ).…”
Section: Discussionmentioning
confidence: 99%